Narcisismo e intolerância na contemporaneidade - CUNHA, Thaís Siqueira (2018)
This paper aims to analyze the intolerance of difference, increasingly present in the contemporary times, based on the concept of narcissism proposed by Freud, read by Lacan. For this, it is evidenced the dynamics in the approximation of the speaker to others, and follows the constitution of the drive subject, which is also inscribed in and by language. The drama that constitutes the speaker is punctuated from an ideal image that reveals the mark that he needed an Other to support him. It is observed, therefore, the division of the self and the features of narcissism, which is also constitutive. With Lacan, it is showed that the Oedipal exits do not count only on an imaginary identification, pure and simple, but count on the lack of object that the image camouflages, considering, beyond the superego, the identification to a trace. The paternal metaphor is situated, which refers to the function of the father, which is at the center of the Oedipus, and its role in the assumption of sex, and in relation to the function of the Ideal of the self. It is reached the point of the constitution on a background of aggressiveness, due to the divergence between the subject and his world, which motivates his desire for the object of desire of the Other. Finally, it is elaborated that intolerance says of a subject trapped in an imaginary identification, a subject that shows some compromise in relation to the phallic norm, to castration, in the relation with the Other, where the narcissistic promotion of the self left little or no room for the difference - which is always sexual.